COVID-19 impact on the assessment methodology of undergraduate medical students: a systematic review of the lessons learned - Machado, Maria Helena; Paredes, Sílvia; Ribeiro, Laura (Frontiers in Education, 2023)
The Covid-19 pandemic had a substantial social, economic, political, and educational impact worldwide. Due to the social contact restrictions, areas such as medical education were highly affected. Assessment in medical education, was already a sensitive topic, and it proved to be even more challenging as different teaching and learning contexts required huge adaptations in a short period. This systematic review provides an overview of the impact of Covid-19 on the assessment of medical students and can serve as a reference to improve this area. We conducted the review based on the PRISMA tool and searched in PubMed, EBSCO, and ScienceDirect. Studies describing the assessment methodologies used during the pandemic were included. Of the 501 initial articles, 18 were included in this review. Collected data was based on the regime, subject, teaching/assessment methodologies, platforms used, grades, students' and teachers' perceptions, and measures to prevent academic dishonesty. The results suggest that technology played a central role during the pandemic, and universities were concerned about the transition to online learning regarding teaching and assessment, but students and teachers should be prepared for it. Formative assessment methodologies and feedback were emphasized, and summative tools were adapted to prevent fraud. Students and teachers were generally satisfied with online learning and assessment, which had no significant difference in the examination scores, but they preferred conventional teaching. The Covid-19 pandemic brought an opportunity to analyse and rethink the medical curriculum. Thus, further investigations are needed on combining traditional and online teaching strategies and emphasis on the assessment.